Ungulate-train collision database - Jasińska, Karolina; Żmihorski, Michał; Krauze-Gryz, Dagny; Kotowska, Dorota; Werka, Joanna; Piotrowska, Diana; Pärt, Tomas (Dryad Digital Repository, 2019)
A database with over 3500 ungulate-train collisions and over 10 000 random localities along Polish railways, used in analyses published in Jasińska et al. Journal of Applied Ecology (2019). The databse is incomplete, however, as we do not own data provided by Polish Railways PKP.